Assessing gamification and corporate sustainability - Al-Kandari, Anwaar (2025)
Purpose : This paper examines the impact of gamification on corporate sustainability, focusing on the role of digital transformation and open innovation within the ecosystem. It aims to highlight how gamification enhances stakeholder engagement and fosters innovation for sustainable development in small and medium enterprises. Design/methodology/approach. A comprehensive literature review and empirical data collection were conducted, utilizing Structural Equation & Modeling (SEM) to assess the interrelationships between gamification, digital transformation, open innovation, ecosystem, and corporate sustainability. Data was analyzed using SPSS and Smart-PLS software, incorporating Confirmatory Factor Analysis (CFA) to verify the constructs. Findings : The findings demonstrate that gamification positively influences open innovation and digital transformation, which in turn contribute to the development of an ecosystem that supports corporate sustainability. The study also reveals that while the ecosystem significantly impacts sustainability, gamification's direct effect on the ecosystem is not statistically significant. Research limitations/implications. This study is limited by its purposive sampling of industry professionals from Kuwait and Bahrain, which may affect the generalizability of the findings to other regions or broader populations. Additionally, potential biases related to self-reported data and cultural perceptions of gamification were not explicitly controlled. Future research should explore different regional and organizational contexts, investigate longitudinal effects, and examine moderating variables such as organizational culture and stakeholder dynamics. Despite these limitations, the study provides valuable insights into the integrated role of gamification, open innovation, and digital transformation in promoting corporate sustainability. Practical implications. The findings offer actionable strategies for small and medium-sized enterprises (SMEs) seeking to enhance corporate sustainability. Organizations should align gamification efforts with broader digital transformation and open innovation initiatives to foster greater stakeholder engagement and ecosystem development. Managers are encouraged to design gamified experiences tailored to different stakeholder groups, integrate digital tools to facilitate collaboration, and cultivate a culture of innovation. Emphasizing value co-creation and long-term ecosystem relationships will strengthen sustainability efforts, particularly in dynamic and technology-driven business environments. Social implications. By integrating gamification, digital transformation, and open innovation, organizations can promote broader stakeholder participation in sustainability initiatives, leading to stronger community engagement and social value creation. Gamified strategies can encourage sustainable behaviors among employees, customers, and partners, fostering a culture of environmental and social responsibility. Additionally, the study highlights the potential for SMEs to contribute to societal goals, such as reducing environmental impact and promoting inclusive growth, by adopting collaborative and technology-driven approaches. Strengthening ecosystem relationships also supports collective action toward social and environmental challenges in the broader community. Originality/value. This study contributes to the limited research on the integration of gamification with corporate sustainability, emphasizing the potential of gamification as a strategic tool for fostering innovation and digital transformation within business ecosystems. The findings offer novel insights into the interplay between these factors, particularly in the context of small and medium enterprises.